Uwarunkowania informatyzacji bankowości spółdzielczej na tle bankowej i parabankowej konkurencji - Zieliński, Tomasz (The Background of Co-Operative Banking Computerization Under Competition from Banks and Parabanks, 2005)
The sector of corporate banking in Poland has developed very dynamically over the last 14 years. One of the very spectacular aspects of that process is information technology. It can not be however considered apart from banking capital resources and competition of other entities. The cooperative form of banking ownership is natural restriction to growing investments in IT technology. Another factor which is essential for cooperative banking is increasing competition of financial and non-financial institutions. Four categories of competitors can be considered: banking, post, quasi-banking and non-financial. Contributing to the same retail market, they can push corporate banks out. The only way to prevent it, is to join the efforts within IT activities. One of the solutions could be the cooperation with an external firm on the terms of outsourcing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 140-150